A quadrinista acidental e o processo de criação da série de quadrinhos Jenericos - Silva, Maria Raquel Alves da (2021)
The present dissertation has an analytical-reflective character about the production process of a series of comics focused on the internet audience titled Jenericos. Using the methodology of genetic criticism to analyze the process of producing comic books and starting from the point of view of a non-author of comics in a new authoring process, this work has as theoretical scope the works of the author Cecília Salles (2008) on genetic criticism, comic book studies by the comic artist Scott McCloud (1995) and an analyticalreflective approach to the creative process of the author in question. The relevance of this study is placed on the possibility of approximation between comic books and other areas of knowledge, using methodological tools typical of visual arts and showing the creation process of a series of comic books by a beginning author, with her artistic route and references, doubts, as well as the paths that led the research to focus on the creation of stories. Structured in three parts, the dissertation is organized this way: the first moment addressing the concepts of genetic criticism, as well as their applications in the work in question; in the second part, introductory notions about comics are covered and, in the final part, an analytical discussion of the entire production process of the comic series.